Studi Perencanaan Bangunan Pengendalian Akresi Dan Abrasi Di Pantai Tanjungwangi Kabupaten Banyuwangi - Hariyoni, Hariyoni; Sisinggih, Dian; Marsudi, Suwanto (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
The Tanjungwangi Beach has a length of 4.52 km has been experiencing with accretion and abrasion in some area due to the dominant wave from northeast direction. Therefore, it is important to take any actions considered as necessary countermeasures to solve the problem of accretion and abrasion. The aim of this study is to understand the distribution of wave direction, the wave with the return period of 25 years H max , H , and the dominance of wave from northeast direction. In term of sediment transport and coastline stability problems, the study location is aiming to find the technical solution. The results indicated that the direction of highest wave comes from the south with rate of 51.505 %, while the highest wave was developed from the northeast direction was 12.596 %. Transported sediment based on data analysis were 13,267.552 m 10 3 /year (abrasion) and 812.239 m /year (accretion). However, the field observation within 10 year period showed that the transport rates are 13,294.955 m 3 /year (abrasion) and 808.018 m 3 3 /year (accretion). Based on the analysis, Tanjungwangi Beach is majorly experiencing with abrasion processes. The revetment structure of natural rock pile was suggested to be set up within the study area.Keywords: Tanjungwangi beach, wave, accretion, abrasion, revetment